Bmi1 Severs as a Potential Tumor-Initiating Cell Marker and Therapeutic Target in Esophageal Squamous Cell Carcinoma - Xiaochen Wang; Kang Li; Maosheng Cheng; Ganping Wang; Hui Han; Fangfang Chen; Wenjing Liao; Zhi Chen; Jianwen Chen; Yong Bao; Liang Peng; Demeng Chen (Stem Cells International)
Esophageal squamous cell carcinoma (ESCC) is a frequent malignant tumor with low 5-year overall survival. Targeting ESCC tumor-initiating cells (TICs) may provide a new research avenue to achieve better therapeutic effects of ESCC. However, the identity and characteristics of ESCC TICs remain poorly understood. Through genetic lineage tracing approach, we found that a group of Moloney murine leukemia virus insertion site 1- (Bmi1-) expressing cell populations present in the invasive front of the esophageal epithelium, providing a continuous flow of tumor cells for ESCC. Subsequently, we found that ablation of Bmi1+ cells from mice with ESCC led to inhibition of tumor growth. In addition, our results demonstrated that PTC-209, an inhibitor of Bmi1, was able to inhibit ESCC progression when combined with cisplatin. In summary, our data suggest that Bmi1+ cells serve as TICs in ESCC.